The Therapeutic Benefit of Allopurinol in the Treatment of Foreign Body Granulomas Caused by Polymethylmethacrylate Microspheres - Luisa Kelmer Côrtes de Barros Silveira; Felipe Ladeira de Oliveira; Thais de Barros Castro Alves; Maria Lourdes Candela Rambaldi; Felipe Cupertino de Andrade; Santuzza de Carvalho Kelmer; Fabio Cuiabano Barbosa (Hindawi Limited, 2012)
Injectable polymethylmethacrylate (PMMA) microspheres are nonbiodegradable and too large for macrophage phagocytosis. There are several complications possible to happen, like chronic nonspecific inflammatory reactions, lip stiffness, infection, and granulomas. The occurrence of granulomas can lead to a not aesthetic result, making some extreme changes in the patient's life. The objective of this case report is to describe the successful treatment of foreign body granulomas caused by polymethylmethacrylate microspheres using allopurinol, an innovative therapy for this condition.